DESIGNING CASE STUDY RESEARCH IN CONSTRUCTION MANAGEMENT - N. Sanda, Yakubu; Natalia A. Anigbogu,; Yohana D. Izam,; Lura Y. Nuhu, (Journal of Surveying, Construction and Property, 2021)
Research methodology is an important and indispensable element in research design. However, designing research strategy such as case study has proven to be a difficult task among research students. Case study is one of the most frequently used qualitative research methodology in the field of construction management; however the design and implementation of case study remains a complex and contentious issue among researchers. Consequently, many students select case study strategy without understanding the array of factors that can affect the outcome of their research. This paper presents a practical, experience-based, step-by-step guide to select, conduct and complete a case study research in construction management. The paper justifies the rationale for adopting case study, explored the various stages in designing case study spanning from the theoretical framework, constructing research themes, data collection and analysis through to validity and reliability issues. This paper contributes in expanding the knowledge of upcoming researchers in the built environment on the design, applications, advantages, disadvantages as well as limitations of case study in construction management researches. The study recommends the research design for students undertaking construction management related studies.